Partial Obstruction of the Endotracheal Tube by the Plastic Coating Sheared from a Stylet - Anirudha Das; Shwetha Chagalamarri; Kim Saridakis (Hindawi Limited, 2016)
A preterm with gestational age of 24 weeks was intubated at day of life 16. The intubation was done in a routine manner with the use of a stylet. It took a significant effort from the clinician to pull the stylet out after intubation. After intubation the respiratory status of the neonate deteriorated requiring significantly greater support. When ventilating and oxygenating the infant was getting progressively difficult, the decision was made to change the endotracheal tube (ETT). The cause for deterioration of respiratory status was then determined to be a sheared piece of plastic from the sheath of the stylet which was lodged in the lumen of the ETT. After removal of the plastic particle, the condition of the infant improved significantly.